Contraception and modern Ireland : a social history, c.1922-92 - Kelly, Laura, 1986- (Cambridge University Press, 2023)
"Contraception was the subject of intense controversy in twentieth-century Ireland. Banned in 1935 and stigmatised by the Catholic Church, it was the focus of some of the most polarised debates before and after its legalisation in 1979. This is the first comprehensive, dedicated history of contraception in Ireland from the establishment of the Irish Free State in 1922 to the 1990s. Drawing on the experiences of Irish citizens through a wide range of archival sources and oral history, Laura Kelly provides insights into the lived experiences of those negotiating family planning, alongside the memories of activists who campaigned for and against legalisation. She highlights the influence of the Catholic Church's teachings and legal structures on Irish life showing how, for many, sex and contraception were obscured by shame. Yet, in spite of these constraints, many Irish women and men showed resistance in accessing contraceptive methods. This title is also available as Open Access"--